ANXIETY ASSOCIATED WITH VISIT TO THE DENTIST - Catalin Pleşea Condratovici; Mariana Ilie; Mutica Mihai; Alina-Pleşea Condratovici; Jana Chihai; Ginel Baciu (Romanian Society of Oral Rehabilitation, 2018)
Aim of the study Anxiety disorder is a mental condition that makes dental treatment difficult both for children and adults. The purpose of this study was to compare the efficacy of behavior management techniques and use of Nitrous Oxide to reduce anxiety in adult pediatric patients Material and methods 170 patients, adults and children in evidence with anxiety disorders were analyzed. Subjects underwent a complex psychological intervention ("tell-show-do" method, music therapy, and respiratory therapy) and in non-responders inhalation with nitrogen protoxide and oxygen was used. Results From the mature subject's analysis, the main reason for low addressability in dentistry for almost half of the subjects is fear. Of the mature subjects, 76% of women and only 24% of men required psychological therapy of anxiety and the effectiveness of psychological methods used to reduce anxiety has a percentage of 46% for men and 34% for women. In the children group there is a very low addressability to the dental services of the people from rural areas. Anxiety related to dental interventions is higher than in older people but the effectiveness of behavioral therapies is very good. In both groups prevalence of dental fear is significantly higher in females Conclusions behavior management techniques like "tell-showdo", music therapy, respiratory therapy are safe and easy to implement. The effectiveness of this method is good in adults (40%) and exceptional in children (90 % success rate).